Aspiration Cytology along with Histomorphological correlation of salivary gland lesions: A 5 years retrospective study - T, Rajini; Megalamane, Supreetha; Das, Subhashish (Annals of Pathology and Laboratory Medicine, 2018)
Background: Fine needle aspiration cytology (FNAC) of salivary glands is one of the most commonly done first line investigations in the head and neck region. A wide variety of benign and malignant tumors originate in the salivary glands and insufficient tumor cells make their diagnosis difficult in some patients. The aim of this study was to evaluate the efficacy of fine-needle aspiration cytology in the diagnosis of salivary gland lesions by correlating cytological findings with histopathology. Methods: All the FNAC slides of salivary gland lesions received at our tertiary hospital for a period of 6years from January 2013 to July 2017were reviewed retrospectively. Histopathological correlation was done for cases wherever available Result: FNAC categorized 50% of the salivary gland lesions as neoplastic and 50% as non-neoplastic lesions. Amongst the neoplastic lesions, 64.28% were benign and 35.72%were malignant cases. Histopathological examination revealed that 66.64% of the cases were benign and 33.36% were malignant. Fine needle aspiration cytology had a sensitivity, specificity and diagnostic accuracy of 75%, 100% and 94.05%, respectively. The positive predictive value and negative predictive value were 100% and 92.75%, respectively. Conclusion: : Fine needle aspiration of the salivary gland is a safe and reliable technique in the primary diagnosis of salivary gland lesions. This study has shown that fine needle aspiration cytology has a high sensitivity, specificity and diagnostic accuracy in diagnosing salivary gland lesions. Being an rninimally invasive procedure, FNA of salivary glands continues to be an important diagnostic tool in the preoperative diagnosis of salivary gland lesions despite few pitfalls in diagnosing due to cytomorphological overlapping.